LEARNERS’ NEED ANALYSIS OF ENGLISH LEARNING MATERIALS FOR ECONOMICS AND BUSINESS STUDENTS OF UNIVERSITAS MUHAMMADIYAH PALEMBANG - Larasati, Finza; Adawiyah, Dita; Yuliani, Sri; Septarini, Dian (English Community Journal, 2022)
The aim of this study was to analyze the learners’ target needs and learning needs for English learning material in the Faculty of Economics and Business, Universitas Muhammadiyah Palembang. This study used qualitative and quantitative research method through questionnaire and interview. The subjects of this study were 49 Economics and Business faculty students who have taken English subject in their previous semester, three lecturers of English, and three alumni users.  The questionnaire was given to the students and the interview was given to the lecturers of English, and alumni users. The result of this study found that the students need the materials that can help them to understand spoken work-related instruction, conduct job interviews, write proposals (projects, plans, etc.), write a job application letter and personal data, do business presentations, read business letters, understand written work-related instructions, negotiate, read work-related literature, read contract/agreement documents, read email, express opinions at business meetings, write business email, write business letters, write contract/agreement documents, write report documents (meetings/sales/finance, etc.), serve customers orally, and to do business conversations through the phone. Furthermore, it could be highlighted from the result of the collecting data that those objectives of the study should be achieved through listening, reading, writing, and speaking activities.